2000
DOI: 10.1099/0022-1317-81-2-327
|View full text |Cite
|
Sign up to set email alerts
|

α6 integrin is not the obligatory cell receptor for bovine papillomavirus type 4

Abstract: Recently, α6 integrin has been proposed as the epithelial cell receptor for papillomavirus. This study investigated whether α6 integrin is the cellular receptor for bovine papillomavirus type 4 (BPV-4), which is strictly epitheliotropic and infects the mucous epithelium of the upper digestive tract. Primary bovine mucosal keratinocytes from the palate of a foetus (PalK) displayed high levels of α6 integrin ; matched primary fibroblasts from the same biopsy (PalF) expressed almost no α6 integrin. However, BPV-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The micro-injury is necessary for the virus to access basal keratinocytes (Liu and Baleja, 2008), where the virus cycle begins (Campo, 1997a). Current studies also show that integrin α6 (CD49f) and integrin 332 (laminin 5) are targets for L1 binding (Sibbet et al , 2000; Florin et al , 2012). …”
Section: Bpv Infection Pathway and Histopathological Alterationsmentioning
confidence: 87%
“…The micro-injury is necessary for the virus to access basal keratinocytes (Liu and Baleja, 2008), where the virus cycle begins (Campo, 1997a). Current studies also show that integrin α6 (CD49f) and integrin 332 (laminin 5) are targets for L1 binding (Sibbet et al , 2000; Florin et al , 2012). …”
Section: Bpv Infection Pathway and Histopathological Alterationsmentioning
confidence: 87%
“…It was speculated that this cleavage is required for cell surface localization of α6 integrin [50]. While data suggest that α6 integrin is required for HPV16 PsV infection, studies conducted with HPV33 and BPV4 concluded that α6 integrin is not required for infection [23, 51]. …”
Section: Binding and Cell Surface Receptors Of Hpv16mentioning
confidence: 99%
“…One candidate that has been suggested based on in vitro studies is α6-integrin, an epithelial cell adhesion molecule [26]. However, some cell lines devoid of α6-integrin are readily infected, so it certainly is not an obligatory cell surface receptor for in vitro infection [27,28]. …”
Section: Entrymentioning
confidence: 99%